Water evaporation during methane hydrate combustion - Santacana Vall, Joan (eScholarship, University of California, 2014)
Methane hydrates are ice-like non-stoichiometric crystalline solids composed of water cages that are stabilized by the presence of a guest methane molecule. They occur naturally in the permafrost and in deep ocean sediments. They represent a potential mega-resource of energy and, at the same time, they can have a substantial potential impact on the environment. This project studies experimentally the formation and direct combustion of methane hydrates. Formation of methane hydrates samples is a complex process that needs precise control due to fragile stability of the hydrates at high pressure within narrow time and temperature ranges. Heat from the combustion process dissociates the hydrate into water and methane, which feeds the methane-air diffusion flame. In this thesis, uniform, repeatable and high quality samples were successfully formed with a clathration of 81.82 ±3.39%. Another achievement was that the samples burned completely and they had three different regimes, an initial one of 1 second based on the propagation of the flame, a second one between 1 and 5 second with a bright and high flame and finally the quasi-steady state regime after 5 seconds until the end of the process. The accomplishment of reaching this quasi-steady state regime permitted the determination of key properties of the combustion behavior. The results show that the burning rate at this regime is 2.5 mg/s*cm2, a flame temperature estimated between 1550 and 2050 K and the novelty of determining the water vapor content versus methane in the flame, which is between 0.5 and 1.5 by molar ratio. Finally the energy balance model showed that 25% of the heat is needed for dissociation of the hydrate and the remaining heat produces approximately 470 kW/m2.